2016
DOI: 10.1016/j.molcel.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

POLD3 Is Haploinsufficient for DNA Replication in Mice

Abstract: The Pold3 gene encodes a subunit of the Polδ DNA polymerase complex. Pold3 orthologs are not essential in Saccharomyces cerevisiae or chicken DT40 cells, but the Schizosaccharomyces pombe ortholog is essential. POLD3 also has a specialized role in the repair of broken replication forks, suggesting that POLD3 activity could be particularly relevant for cancer cells enduring high levels of DNA replication stress. We report here that POLD3 is essential for mouse development and is also required for viability in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 27 publications
5
37
0
Order By: Relevance
“…This is consistent with POLD3 not being essential for RF progression, as is the case of the Pol32 budding yeast counterpart12. Importantly, however, POLD3 is essential in S. pombe 21 and mammals, provided the recent report showing that POLD3 knock out leads to embryonic lethality in mic37. Certainly, the phenotypes described here must be a consequence of a great reduction rather than a complete ablation of the protein after siRNA knockdown.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is consistent with POLD3 not being essential for RF progression, as is the case of the Pol32 budding yeast counterpart12. Importantly, however, POLD3 is essential in S. pombe 21 and mammals, provided the recent report showing that POLD3 knock out leads to embryonic lethality in mic37. Certainly, the phenotypes described here must be a consequence of a great reduction rather than a complete ablation of the protein after siRNA knockdown.…”
Section: Discussionsupporting
confidence: 87%
“…4). In agreement with this conclusion, it has just been reported that POLD3-depletion also induces replication stress and DNA damage in mice37.…”
Section: Discussionsupporting
confidence: 83%
“…In yeast, specific chromosome gains, cause specific DNA replication and repair defects, indicating that altered expression of specific genes located on the aneuploid chromosome is responsible for the observed defects (Sheltzer et al, 2011; Zhu et al, 2012). In mammalian cells, multiple DNA replication factors such as the ssDNA binding protein RPA and the lagging strand DNA polymerase δ have been shown to be haploinsufficient (Murga et al, 2016; O’Driscoll, 2008). Furthermore, aneuploid cells downregulate the expression of DNA replication proteins, such as the MCM helicases (Passerini et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…7g), consistent with a stabilizing role for POLD3 (ref. 26). Clones c1–c3 displayed accelerated telomere shortening at ~PD 25 compared to the empty guide control, whereas clone c4 had a more minor phenotype (Fig.…”
Section: Pold3 Is Critical For Alt Telomere Maintenancementioning
confidence: 99%